The characterization of uterine calcium transport and metabolism during eggshell calcification of hens laying high or low breaking strength eggshell - Ying-ying Yang; Dong Dai; Hai-jun Zhang; Shu-geng Wu; Guang-hai Qi; Jing Wang (Poultry Science)
This study investigated the differences of calcium transport-related proteins and metabolites in the uterus of hens with different breaking strength eggshell during the eggshell calcification. A total of 200 Hy-Line Brown laying hens, aged 75 weeks, were selected and categorized into two groups based on the eggshell breaking strength: a high-strength group (HS, > 42 N) and a low-strength group (LS, < 32 N). Laying hens were sampled at 1 h, 7 h (the initiation stage of eggshell calcification), and 17 h (the growth stage of eggshell calcification) post-oviposition (PO). The LS group showed a decreased thickness, weight and weight ratio of eggshells, accompanied with ultrastructural deterioration and total Ca reduction. The expression levels of ATP2A3, ATP2B2, SLC8A1, and SLC8A3 were significantly increased in the HS at 17 h PO when compared to 1 h and 7 h PO, while no significant changes were observed in the LS. At 7 h PO, the LS group had lower uterine mucosa calcium levels, higher TRPV6 protein expression, and lower CALB1 protein expression. In the HS group, uterine metabolites showed a significant increase in glutathione, citrulline, and proline at 7 h PO, whereas, at 17 h PO, the tricarboxylic acid cycle pathway was significantly enriched. These findings suggest that uterine calcium transport activity is relatively subdued during the initiation stage of eggshell calcification, focusing on redox repair activities to maintain homeostasis for mammillary knobs formation. Subsequently, uterine calcium transport activity becomes highly active during the growth stage of eggshell calcification, primarily supporting rapid calcium transport through enhanced energy metabolism. In aged laying hens, the lower eggshell breaking strength may be attributed to decreased calcium levels during the initiation stage and imbalanced redox during the growth stage, which could affect calcium transport and lead to a weak ultrastructure during the calcification period.